Simulation of Wind Effect on Solar Panels - Neto, Mateus Manuel; Pham, Van Thang; Luu, Thi Lan Anh; Pham, Phi Hung; Nguyen, Ngoc Trung; Vo, Thach Son (Old Journal, 2018)
The design and installation of photovoltaics system depend on the location climate condition. In this study, we investigate to effect of wind as velocity, inclined angle of solar panels,...to the solar cell system in Angola through the using the Computational Fluid Dynamic (CFD) software ANSYS Fluent. The simulated using solar cells system has power of 300W consist of 25 solar panels with dimension of each panel is 1.96m in length, 0.99m in width and 0.046m in depth. Panels are placed with 5 rows and 5 columns, where these solar panels are designed to be placed within a 0.002m gap between them. Results show that inclined angle of solar panels β = 30º within velocity of wind 9m/s and horizontal wind direction (attack angle α equal zero degree). The lower left corner in the direction of the wind is the largest distortion of about 0.685mm. The equivalent stress is found maximum at vertical bar of support of solar panel. The maximum value is about 7.46x104Pa. This value is lower than the limit stress of aluminum alloy (7.1x109Pa).